2014
DOI: 10.5539/mas.v8n1p88
|View full text |Cite
|
Sign up to set email alerts
|

Driving Behavior and Traffic Safety: An Acceleration-Based Safety Evaluation Procedure for Smartphones

Abstract: Traffic safety and energy efficiency of vehicles are strictly related to driver's behavior. The scientific literature has investigated on some specific dynamic parameters that, among the others, can be used as a measure of unsafe or aggressive driving style such as longitudinal and lateral acceleration of vehicle. Moreover, the use of modern mobile devices (smartphones and tablets), and their internal sensors (GPS receivers, three-axes accelerometers), allows road users to receive real time information and fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(44 citation statements)
references
References 11 publications
1
43
0
Order By: Relevance
“…Another category of driving events that are of interest in [238] x x Thresholding. [239] x x x Thresholding. [83], [240] x x Thresholding.…”
Section: Driver Behavior Classificationmentioning
confidence: 99%
“…Another category of driving events that are of interest in [238] x x Thresholding. [239] x x x Thresholding. [83], [240] x x Thresholding.…”
Section: Driver Behavior Classificationmentioning
confidence: 99%
“…FCD data have also been used to establish unsafe driving behaviors in Axer and Friedrich [22]. Other works on traffic safety based on FCD are Biral et al [23], Vaiana et al [24], and Guido et al [25]. Kerner et al [26] showed that 1.5% of FCD penetration rate can be enough to detect an incident in a traffic center with a probability of 65%.…”
Section: State Of the Art And Contributionmentioning
confidence: 99%
“…In [18] has been proposed a theoretical framework in which acceleration behavior can be analyzed in order to detect aggressive behavior. The limits of these accelerations are related to the edges of the friction circle (also called ellipse of adherence), which depend on tire characteristics and road surface condition.…”
Section: Related Workmentioning
confidence: 99%